2007
DOI: 10.1177/1367493507079558
|View full text |Cite
|
Sign up to set email alerts
|

Parental assessment and management of children's postoperative pain: a randomized clinical trial

Abstract: As day case surgery increases, one needs to improve the management of pain in children at home. This study wished to determine whether the use of a self-report pain scale would result in children receiving more analgesia. Eighty-eight children aged four to 12 years undergoing tonsillectomy, whose parents agreed they could participate, were randomly assigned into two groups. Group A received the routine postoperative advice and a three-day prescription of paracetamol, ibuprofen and codeine. In addition, group B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 14 publications
1
51
0
1
Order By: Relevance
“…With changes to the delivery of health care, increasing numbers of children undergo surgery on an outpatient basis, which leaves the responsibility for management of postoperative pain in the hands of parents. Unfortunately, research has repeatedly documented that parents struggle with optimal pain management of children and, in fact, tend to undermedicate children's acute surgical pain [1,[4][5][6][7][8][9][10][11][12]. The research by our group not only has documented parental undertreatment of children's postoperative pain [1] but also has identified that parental attitudes regarding analgesic use for children are a barrier to optimal pain management.…”
Section: Millions Of Children Undergo Surgery In the Unitedmentioning
confidence: 87%
“…With changes to the delivery of health care, increasing numbers of children undergo surgery on an outpatient basis, which leaves the responsibility for management of postoperative pain in the hands of parents. Unfortunately, research has repeatedly documented that parents struggle with optimal pain management of children and, in fact, tend to undermedicate children's acute surgical pain [1,[4][5][6][7][8][9][10][11][12]. The research by our group not only has documented parental undertreatment of children's postoperative pain [1] but also has identified that parental attitudes regarding analgesic use for children are a barrier to optimal pain management.…”
Section: Millions Of Children Undergo Surgery In the Unitedmentioning
confidence: 87%
“…Despite these findings, parents have been critiqued for undertreating children's pain by withholding prescribed analgesics following surgery (Fortier et al, 2009). Further, many studies suggest that most parents give less than prescribed analgesic doses after surgery in a manner that correlates only poorly to moderately with their children's reported pain intensity (Kankkunen et al, 2003;Rony et al, 2010;Stewart et al, 2012;Vincent et al, 2012;Warnock and Lander, 1998;Zisk et al, 2008;Hamers and Abu-Saad, 2002;Helgadottir and Wilson, 2004;Unsworth et al, 2007;Wiggins and Foster, 2007;Huth and Broome, 2007). Many discontinue analgesics even when pain is ongoing (Warnock and Lander, 1998;Hamers and Abu-Saad, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…Of these, only 131 (9.2%) were administered during study period. The median number of prescribed doses was 18 (IQR, [10][11][12][13][14][15][16][17][18][19][20], and the median number of administered doses was 1 (IQR, 0-3).…”
Section: Reported Morphine Use At Homementioning
confidence: 99%
“…It has been shown that there is little correlation between the administration of analgesics and the level of pain evaluated by the parents, with or without the use of pain scales. [11][12][13] In addition, parents' perceptions about analgesics can influence their administration. Rony et al 14 demonstrated that parents with more attitudinal barriers towards analgesics administered less of these medications.…”
mentioning
confidence: 99%